2017
DOI: 10.1002/cbin.10765
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‐488‐3p sensitizes malignant melanoma cells to cisplatin by targeting PRKDC

Abstract: Deregulation of microRNAs (miRNAs) has been implicated in drug resistance in various types of cancers, including malignant melanoma (MM). MiR-488-3p has been reported as a tumor suppressor in several cancers. However, the exact expression patterns of miR-488-3p and the precise molecular mechanisms underlying its role in MM remain largely unknown and require further investigation. In this study, we demonstrated that miR-488-3p is significantly downregulated in MM clinical specimens and cell lines. Ectopic expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 25 publications
1
18
0
Order By: Relevance
“…Since the reverse of miR‐488‐3p effect on ESCC caused by ZBTB2 was partial, we speculated that miR‐488‐3p might have alternate target in ESCC. A previous study reported that miR‐488‐3p could target PRKDC to sensitize melanoma cells to cisplatin . PRKDC has been reported to regulate DNA damage repair, apoptosis, proliferation and cell cycle in multiple cancers, and has also been reported to relate to radioresistance in ESCC .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the reverse of miR‐488‐3p effect on ESCC caused by ZBTB2 was partial, we speculated that miR‐488‐3p might have alternate target in ESCC. A previous study reported that miR‐488‐3p could target PRKDC to sensitize melanoma cells to cisplatin . PRKDC has been reported to regulate DNA damage repair, apoptosis, proliferation and cell cycle in multiple cancers, and has also been reported to relate to radioresistance in ESCC .…”
Section: Resultsmentioning
confidence: 99%
“…A number of studies have reported that miRNAs exerted antitumor functions in cancers in such manner, including in ESCC . MiR‐488‐3p has also been reported to inhibit tumor progression by targeting oncogene in glioma and melanoma . In our study, we predicted through TargetScan the potential targets for miR‐488‐3p, among which we chose ZBTB2 for further exploration.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…mi-RNA 101 overexpression has been shown to downregulate ATM and DNA-PKcs and to sensitize tumor xenograft to IRs and pancreatic cancer cells to gemcitabine [44,45]. Another study used a mi-RNA 488-3p to sensitize in vitro malignant melanoma cells to cisplatin by targeting the PRKDC gene coding for DNA-PKcs [46]. This strategy of inhibition is still far from clinical application.…”
Section: Targeting Dna-pk With Inhibiting Moleculesmentioning
confidence: 99%
“…There is evidence that a single miRNA may have more than hundred mRNA targets while an individual mRNA may be targeted by multiple miRNAs [127]. Findings from a recent report demonstrated that miR-488-3p was capable of sensitizing malignant melanoma cells to cisplatin treatment by targeting transcripts synthesized from PRKDC (the gene encoding DNA-PKcs) thus leading to a decline in its protein expression levels [128]. In addition, miR-21 was shown to provoke an increase in the activity of DNA-PKcs by targeting GSK3B, thus stimulating an increase in DSBs repair leading to radioresistance observed in various tumor cell lines [129].…”
Section: <Fig 3>mentioning
confidence: 99%